CULTIVO DE MELANCIA EM SISTEMA DE SEMEADURA DIRETA NA COVA COM USO DE POLIMERO RETENTOR DE ÁGUA - Nunes, Igor Barros; Espindola, Gabriella Almeida dos Santos; Silva, Pedro Henrique Ortiz3; VIEIRA, Jéssica Dionizio; Rego, Norton Hayd (ANAIS DO ENIC, 2025)
-